(untitled) - Ministry of land management, Uran planning and construction (Cambodia, 2001)
This is provide information framework conditions, getting stared, steps and procedures of plup ( preparation of field work, situation analysis in the community, prreliminary identification and scrêning of options, ..) and PLUP under special conditions.
Keywords: Land use, Rural,Regional planning,Sử dụng đất nông thôn,Khu vực quy hoach; Planning; Cambodia,Cambodia,Campuchia,Campuchia